Ethics of Using Artificial Intelligence in Journalism - KHAYOON, Dr. AHMED JABER (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
The research aimed to identify the ethics of using artificial intelligence in journalism by measuring the level of journalists’ use of artificial intelligence tools in journalistic work, their level of awareness of the ethical dimensions associated with this use, and the extent of their commitment to professional journalistic standards when using these tools. The research also sought to reveal the correlational relationship between the use of artificial intelligence tools and ethical awareness, and between awareness of artificial intelligence ethics and commitment to professional journalistic standards.The research adopted the descriptive correlational approach and used the questionnaire as a tool for collecting data from a purposive sample consisting of (180) Iraqi journalists working in print and electronic journalistic institutions and digital newsrooms. The research instrument consisted of three main axes: the use of artificial intelligence tools in journalistic work, awareness of the ethical dimensions of using artificial intelligence, and commitment to professional journalistic standards. The reliability of the instrument was verified using Cronbach’s Alpha coefficient, as the overall reliability coefficient reached (0.89). The results of the research showed that the level of journalists’ use of artificial intelligence tools in journalistic work was high, with an overall arithmetic mean of (3.58). The level of awareness of the ethical dimensions of using artificial intelligence was also high, with an arithmetic mean of (4.02). The results also showed that the level of commitment to professional journalistic standards when using artificial intelligence was high, with an arithmetic mean of (3.94). The results further revealed a positive, statistically significant correlation between the use of artificial intelligence tools and ethical awareness, as the correlation coefficient reached (0.52), and a positive, statistically significant correlation between ethical awareness and commitment to professional journalistic standards, as the correlation coefficient reached (0.68).The research concluded that the responsible use of artificial intelligence in journalism is not achieved merely by possessing technical tools, but requires clear ethical awareness, continuous human review, and organized editorial policies. The research recommended the necessity of developing professional guidelines for the use of artificial intelligence within journalistic institutions, training journalists to verify its outputs, protecting the privacy of sources, and disclosing its use when it has an influential role in producing journalistic content.